The Effectiveness of Using Movies “Frozen” to Improve Students Vocabulary In Pandemic Covid 19 - Aguslina Giawa; Fara Fadhila; Mia Audina Simbolon; Madina Madina (Peneliti.net, 2021)
The formation of vocabulary is an important part of any language learning process. The most crucial language feature for students to master is vocabulary, since it is the key to understanding what they hear and read and then speaking effectively with others. The researcher evaluates the effectiveness of one of the alternative teaching methodologies using the film